(untitled) (Northern International Medical College Journal, 2020)
Community-acquired pneumonia (CAP) is a potentially serious infection and is the single commonest and leading cause of death in under 5 children in developing countries. But the crucial first step in tackling childhood pneumonia is being able to diagnose it accurately, particularly after introduction of 2 effective vaccines against two major pathogens responsible for childhood bacterial pneumonia. Radiology and determination of hypoxia by pulse oximetry have been considered the optimal methods for diagnosing pneumonia. This review article has updated the important aspects of childhood pneumonia in developing countries. Early recognition and prompt, appropriate and adequate management can reduce the case fatality as well as morbidity associated with pneumonia. Northern International Medical College Journal Vol. 11 No. 1 July 2019, Page 406-410